Pengaruh Perbedaan Jenis dan Konsentrasi Sumber Nitrogen (NaNO3 dan urea) terhadap Produksi Biomasa Spirulina Platensis - Yustinus Selis Toron; Sharfan Dwicahyanto; Wardalia Wardalia; Iqbal Syaichurrozi (Eksergi, 2023)
The goal of this study was to investigate the effect of the concentration and the type of nitrogen sources in the cultivation medium on the production of biomass and biochemical content (carbohydrates, proteins, fats) in the Spirulina platensis biomass. Types of nitrogen sources included NaNO3 and urea, where the concentrations were varied from 0.5 to 3.5 g/L. The results showed that the use of urea tended to produce more S. platensis biomass than the use of NaNO3. The best concentrations that produced the highest biomass were NaNO3 2.5 g/L (biomass 0.6745 g/L) and urea 0.5 g/L (biomass 0.7158 g/L). The use of urea also tended to produce a higher specific growth rate and a shorter doubling time than the use of NaNO3. The high concentration of nitrogen sources caused the pH of the medium to increase more rapidly due to the accumulation of ammonium in the medium. Using NaNO3 can produce biomass with a higher protein content (28.34-36.98%) than using urea (25.86-33.52%).